Exploring caregivers’ experiences of caring for men with advanced prostate cancer in a resource-poor setting: a qualitative serial interview study - Salifu, Yakubu; Almack, Kathryn; Caswell, Glenys (2018)
Background: Family caregivers who assume the responsibility of care for patients living with advanced diseases could have challenges especially in resource-poor settings. The bulk and responsibility for care are predominantly provided by the family caregivers within the informal sector. The family caregivers, therefore, could be described as the ‘general practitioners’ of the patients at home. Using a qualitative study, the experiences of the family caregivers caring for men with advanced prostate cancer were explored.